Prevalence and Correlates of Self-Reported Cardiovascular Diseases Among a Nationally Representative Population-Based Sample of Adults in Ecuador in 2018 - Pengpid S; Peltzer K (Vascular Health and Risk Management, 2021)
Supa Pengpid,1,2 Karl Peltzer3 1ASEAN Institute for Health Development, Mahidol University, Salaya, Nakhon Pathom, Thailand; 2Department of Research Administration and Development, University of Limpopo, Turfloop, South Africa; 3Department of Psychology, University of the Free State, Bloemfontein, South AfricaCorrespondence: Karl PeltzerDepartment of Psychology, University of the Free State, Bloemfontein, South AfricaEmail kfpeltzer@gmail.comBackground: This study aimed to determine the prevalence and correlates of self-reported cardiovascular diseases (SRCVDs) among adults in Ecuador.Methods: National cross-sectional survey data of 4638 persons aged 18– 69 years in Ecuador were analysed. Research data were collected with an interview-administered questionnaire, physical and biochemical measurements.Results: The prevalence of SRCVDs was 8.7%, 8.5% among men and 8.9% among women. In adjusted logistic regression analysis, being Montubio (adjusted odds ratio-AOR: 1.66, 95% confidence interval-CI: 1.10– 2.50), family alcohol problems (AOR: 1.78, 95% CI: 1.19– 2.65), past smoking tobacco (AOR: 1.36, 95% CI: 1.02– 1.81), and poor oral health status (AOR: 1.74, 95% CI: 1.19– 2.54) were associated with SRCVD. In addition, in unadjusted analysis, older age, alcohol dependence, obesity, and having hypertension were associated with SRCVD.Conclusion: Almost one in ten persons aged 18– 69 years had SRCVD in Ecuador. Several associated factors, including Montubio by ethnicity, family alcohol problems, past smoking, and poor oral health status, were identified, which can be targeted in public health interventions.Keywords: chronic conditions, lifestyle factors, cardiovascular disease, adults, Ecuador